Optimisation of the filling process in counter-gravity casting - Papanikolaou, Michail; Saxena, Prateek; Pagone, Emanuele; Salonitis, Konstantinos; Jolly, Mark R. (Institute of Physics (IOP), 2020)
Metal casting is one of the most energy-intensive manufacturing processes with limited resource efficiency. To solve the problem of high energy consumption, a novel counter-gravity casting process has been earlier introduced. This process also referred to as CRIMSON (Constrained Rapid Induction Melting Single Shot Up-Casting) makes use of melting metal, just enough to fill one mould cavity at a time. The molten metal is subsequently pushed into the mould with the help of a piston, using a counter-gravity controlled method. Although CRIMSON has been proven to be a highly efficient process with the potential to produce high quality final cast products, there is still room for optimisation of the process. The objective of this investigation is to estimate the optimum ingate velocity in order to ensure smooth filling of the mould and eventually reduce turbulence and the likelihood of defects in the final cast product. For this purpose, a computational framework integrating a CFD solver and an optimisation algorithm has been developed. The obtained results suggest that the optimised ingate velocity can contribute towards the smooth filling of the mould and effectively contribute towards the reduction of entrained air and surface defect concentration in the final cast product.